Exploring the Potential of Drug Repurposing: Detection of Cystic Fibrosis Transmembrane Conductance Regulator as a Biomarker in Breast Cancer Patients (Precision Medicine Communications, 2023)
Despite the advancements in cancer treatment and the benefits of personalized medicine, breast cancer (BC) remains a significant health concern. Moreover, conventional treatment options are costly and often associated with severe side effects, highlighting the need to identify new biomarkers and innovative treatment strategies for BC. Drug repurposing presents an approach that expands the therapeutic window further to mitigate the financial burden and minimize the potential harm caused by existing anticancer drugs. In the present study, we aim to suggest noncancerous FDA-approved drugs for repurposing, through molecular docking studies in BC, after their target cystic fibrosis transmembrane conductance regulator protein (CFTR) detection in BC. We used a drug repurposing approach to identify the target protein CFTR and drugs that target CFTR. MOE (molecular operating environment) was used to analyze the interaction between CFTR and its targeting drugs. For experimental work, we did Immunofluorescence staining on BC tissue. We found that glyburide and tezacaftor were the top antagonist and agonists, respectively. We detected CFTR expression in all ten samples except Triple-Negative Breast Cancer (TNBC). CFTR and estrogen receptor alpha co-expressed at 6.78%, suggesting a potential relationship. High-grade tumors showed CFTR expression below 8%, indicating CFTR down-regulation and its role in tumor aggressiveness. Our study is a preliminary step towards in-vitro and in-vivo experiments on repurposing CFTR-targeting drugs in BC. Glyburide may inhibit CFTR's estrogen production, while tezacaftor can enhance CFTR action to overcome tumor aggressiveness.
Keywords: Breast cancer; new biomarker; drug repurposing; CFTR; glyburide; tezacaftor